Penguatan Standar dan Kompetensi Guru dalam Kurikulum Berbasis Hasil (Outcome-Based Education) - Muhammad Rajiannor; Nisa Muflihah; Suriagiri (Jurnal Pendidikan Agama Islam, 2026)
Teacher standards and competencies are crucial aspects in improving the quality of education, particularly in responding to the demands of an outcome-based curriculum (Outcome-Based Education/OBE) that emphasizes measurable and relevant learning outcomes. This study aims to examine the strengthening of teacher standards in formulating and implementing an outcome-based curriculum. This research employs a qualitative approach through a literature study by utilizing secondary data from books and journals analyzed descriptively. The results of the study indicate that strengthening teacher standards is a key factor in the successful formulation of an outcome-based curriculum, as teachers play a strategic role in determining learning outcomes, developing instructional strategies, and designing aligned assessment systems. Integrated teacher competencies enable the realization of a curriculum that is not only material-oriented but also focused on students' actual abilities. Therefore, the continuous improvement of teacher standards and competencies becomes an essential step in producing a curriculum that is effective, adaptive, and oriented toward learning outcomes.